Legalitas Skb Tentang Pedoman Implementasi Pasal Tertentu dalam UU ITE Ditinjau dari UU Pembentukan Peraturan Perundang-Undangan - Marcella Julita; Ade Adhari (UNES Law Review, 2023)
The SKB ITE was established as a guideline for the implementation of specific articles within the Electronic Information and Transactions Law (UU ITE) that were deemed inherently confusing in their execution. However, the legality of the SKB ITE remains a current issue, particularly concerning its issuance procedures and status. This research employs a normative legal research approach. The findings indicate that SKB ITE serves as an implementation guideline for the UU ITE that lacks a legal basis and violates the Law on Legislation Formation, as its establishment does not conform to the prescribed mechanisms, thus SKB ITE must be declared null and void. Nonetheless, a subsequent issue arises regarding the divergent interests between legislators, regulatory observers, and all of whom are demanding amendments to the UU ITE. Considering the invalidity of the SKB ITE, the most appropriate course of action would be to revise the UU ITE by incorporating the substantive aspects outlined in the SKB ITE and aligning it with the provisions of cybercrime in the New Indonesian Criminal Code. Through these changes, the need for a implementation guideline for the UU ITE can be addressed, thereby enhancing the effectiveness of its implementation and reducing societal controversies surrounding it